2005
DOI: 10.1016/j.ssc.2005.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and electron energy-loss spectra of Sr0.35CoO2

Abstract: The electronic structure of Sr 0.35 CoO 2 , structurally analogous to the layered Na x CoO 2 , has been evaluated using the local spin density approximation (LSDA). We find that evident c-dispersions appear in both the e ' g and a 1g Co-derived bands, demonstrating the existence of a notable interplanar interaction in Sr 0.35 CoO 2 . The LSDA+U calculation reveals that the electronic structure, in particular the band splitting between the spin-up and spin-down electrons, changes evidently along with the increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
(38 reference statements)
2
5
0
Order By: Relevance
“…3͑a͒, both ab and c exhibit metallic behaviors in the whole temperature range, consistent with the band structure calculation. 27 The ab behavior is qualitatively the same as that in polycrystalline Sr 0.35 CoO 2 samples. 17,15 At room temperature the resistivity is only slightly anisotropic with c Ϸ 6 ab , in agreement with an anisotropic ratio c / ab Ϸ 3 for Na 0.71 CoO 2 crystal and a resistivity anisotropy ͑ c / ab ͒ of 8 by electronic structure calculations for NaCo 2 O 4 .…”
Section: A Magnetic Susceptibilitysupporting
confidence: 58%
See 1 more Smart Citation
“…3͑a͒, both ab and c exhibit metallic behaviors in the whole temperature range, consistent with the band structure calculation. 27 The ab behavior is qualitatively the same as that in polycrystalline Sr 0.35 CoO 2 samples. 17,15 At room temperature the resistivity is only slightly anisotropic with c Ϸ 6 ab , in agreement with an anisotropic ratio c / ab Ϸ 3 for Na 0.71 CoO 2 crystal and a resistivity anisotropy ͑ c / ab ͒ of 8 by electronic structure calculations for NaCo 2 O 4 .…”
Section: A Magnetic Susceptibilitysupporting
confidence: 58%
“…Moreover, a band structure calculation of Sr 0.35 CoO 2 reveals evident c dispersions, demonstrating the existence of a notable interplanar interaction. 27 This implies Sr 0.35 CoO 2 is highly three dimensional. The slight resistivity anisotropy of Sr 0.35 CoO 2 may be correlated with this relative isotropic interaction.…”
Section: B Resistivitymentioning
confidence: 99%
“…17 The resistivity of Sr 0.35 CoO 2 is 8.83 m⍀ cm at 300 K. This agrees with the data published by Ishikawa et al 16 The resistivity of Sr 0.35 CoO 2 is larger than that of ␥-Na 0.7 CoO 2 over the whole temperature range.…”
Section: B Specific Heatsupporting
confidence: 90%
“…Its Seebeck coefficient is comparable to that of ␥-Na 0.7 CoO 2 , and the resistivity shows a metallic behavior, in agreement with the band-structure calculation. 17 Structural analysis suggested that Sr x CoO 2 has hexagonal symmetry, similar to ␥ -Na x CoO 2 ͑P6 3 / mmc͒. Two superstructures arising respectively from the ordering of intercalated Sr and a periodic structural distortion were observed in Sr 0.35 CoO 2 .…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation